Isolation and purification of osthole and imperatorin from Fructus Cnidii by semi-preparative supercritical fluid chromatography. Issue 8 (9th May 2017) - Zhang, Liheng; Sun, Ailing; Li, Aifeng; Kang, Jingjing; Wang, Yancui; Liu, Renmin
ABSTRACT: Fructus Cnidii, the dried ripe fruit of Cnidium monnieri (L.) Cusson ., has been widely used in traditional Chinese medicine. Osthole and imperatorin are the main active ingredients of Fructus Cnidii and had been found of antispasmodic, anti-HIV, anti-fungal, anti-viral, anti-tumor, anti-mutagenic, anti-arrhythmic, hypotensive, and broad-spectrum antimicrobial effects. A supercritical fluid chromatography (SFC) method for isolation and purification of osthole and imperatorin from Fructus Cnidii was established in this work. The separation conditions, including the stationary phase, the organic modifier, the composition and the flow rate of the mobile phase, column backpressure and column temperature, were optimized on analytical scale at first. And then a semi-preparative SFC (SP-SFC) method was developed based on the conditions of analytical scale SFC. SP-SFC was accomplished on YMC-Pack NH2 column. Ethanol was used as the modifier and its percentage in the mobile phase was 3%. The flow rate of the mobile phase was 20 mL/min, column backpressure was 13 MPa, column temperature was 318 K, detection wavelength was 310 nm, and injection volume was 0.2 mL. Under the optimum conditions, osthole and imperatorin were obtained with high purities as determined by high performance liquid chromatography. The chemical structures of the obtained compounds were identified by nuclear magnetic resonance and mass spectrum analysis. GRAPHICAL ABSTRACT: